2021
DOI: 10.1186/s12933-020-01195-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Mediterranean lifestyle, metabolic syndrome and mortality: a whole-country cohort in Spain

Abstract: Background Evidence is limited about the joint health effects of the Mediterranean lifestyle on cardiometabolic health and mortality. The aim of this study was to evaluate the association of the Mediterranean lifestyle with the frequency of the metabolic syndrome (MS) and the risk of all-cause and cardiovascular mortality in Spain. Methods Data were taken from ENRICA study, a prospective cohort of 11,090 individuals aged 18+ years, representative o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 69 publications
2
49
0
Order By: Relevance
“…However, adherence to a "meat/Western" pattern (which is characterized by a high loading of red meat, processed meat, animal fat, eggs, and sweets) increased the risk of metabolic syndrome in stratified analyses based on either geographical region (Asia, Europe, America) or study design [14]. A previous study found that a Mediterranean diet, which is characterized as rich in vegetables, fruit, whole grains, cereal, fish, and seafood products, was associated with a lower frequency of metabolic syndrome and reduced all-cause mortality [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…However, adherence to a "meat/Western" pattern (which is characterized by a high loading of red meat, processed meat, animal fat, eggs, and sweets) increased the risk of metabolic syndrome in stratified analyses based on either geographical region (Asia, Europe, America) or study design [14]. A previous study found that a Mediterranean diet, which is characterized as rich in vegetables, fruit, whole grains, cereal, fish, and seafood products, was associated with a lower frequency of metabolic syndrome and reduced all-cause mortality [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Noel et al [18] found that a traditional dietary pattern rich in rice, beans, and fat, and sweets rich in sugar, sugary drinks, and dairy desserts was associated with a higher probability of having MS and low concentrations of HDL-cholesterol. In this context, the Mediterranean diet has been presented as the main element in the treatment of MS [2][3][4][5][6][7].…”
Section: Hyperglycemiamentioning
confidence: 99%
“…Thus, lifestyle changes are undoubtedly necessary to minimize this problem and they necessarily go through an increase in the practice of physical exercise and the consequent reduction in sedentary activities (watching television, playing computer, playing with cell phones, etc.). Changes in diet, especially in this age group, are essential, since energy-dense foods are often used, which end up providing a lot of calories; other measures must be taken, such as the use of drugs or other more specific treatments, when the goals are not achieved at all with the lifestyle changes mentioned above [4][5][6][7].…”
Section: Strategies For the Treatment And Prevention Of Metabolic Syndromementioning
confidence: 99%
See 2 more Smart Citations